Outcome of patients with newly diagnosed systemic light-chain amyloidosis associated with deletion of 17p - Wong, Sandy; Hegenbart, Ute; Schönland, Stefan (Clinical lymphoma, myeloma & leukemia, 2018)
Introduction - Deletion 17p (del 17p) portends a poor prognosis in myeloma, but its significance in light-chain amyloidosis is unknown. - Patients and Methods - We identified patients with light-chain amyloidosis and del 17p at diagnosis, and analyzed presenting characteristics, treatments, and clinical outcomes. All had baseline biopsy results showing amyloid and serologic and marrow studies, including standard fluorescence in-situ hybridization determinations of del 17p using commercial probes. Consensus criteria for hematologic and organ involvement, progression, and response were used. Kaplan-Meier (log rank) analyses and Cox regression analysis of baseline variables were used to identify predictors of overall and progression-free survival (PFS). Six-month landmark analyses were performed to assess the impact of treatment-related variables. - Results - We identified 44 patients from 7 countries with median marrow and del 17p plasma cells of 22% (range, 3%-100%) and 30% (2%-93%). Ninety-five percent had cardiac involvement, including 44% stage III. Two-thirds of the patients initially received bortezomib-based therapy. Forty-nine percent of patients experienced complete response or very good partial response, with median time to best response of 4 months (range, 1-28 months). Median overall survival and PFS were 49 and 32 months. Cardiac stage and hematologic response were the key predictors of outcomes. Patients with > 50% and ≤ 50% del 17p in clonal plasma cells had median survivals of 28 and 52 months, respectively (P = .08). In landmark analyses, only hematologic response predicted both overall survival and PFS. - Conclusion - Cardiac stage, hematologic response, and del 17p percentage impact outcomes in these cases. Emphasis should be placed on optimizing supportive care and achieving a deep hematologic response.
Gesehen am 03.04.2020